Prevalence of compulsion in migraine patients and its association with analgesic abuse - Barros , Maria Clara Lopes de; Braz , Ana Carolina Monteiro; Pereira Filho, Júlio César Cimino; Ribeiro , Matheus Henrique Vieira; Sousa , Matheus Silva; Santos , Vinícius Henrique dos; Silva , Danilo Jorge da; Jurno , Mauro Eduardo (Headache Medicine, 2022)
IntroductionMigraine, is one of the most prevalent types of headaches, affects around 15% of people worldwide, more common among women, and causes a great effect in the quality of life of the individual. The diagnosis criteria of this disease is due to its duration and other characteristics such as phonophobia, photophobia, unilateral, pulsatile and intense crisis, nausea and vomiting, which can be preceded by aura and premonitory symptoms. With the purpose to ease those symptoms, the patients have a drug overuse. The medication-overuse headache (MOH) is an emerging problem, due to the possibility of developing psychiatric disorders like obsessive compulsive disorder (OCD) and impulsivity. Impulsivity consists in actions where the individual does not reflect upon it and make decisions fast, without planning or analyzing the case in the long term. Compulsion is defined as repetitive actions with the intention to ease anxiety or an uncomfortable situation.ObjectiveDetermine a prevalence of OCD in migraine patients, evaluating different scopes of it, including the association or not with drug abuse.MethodsA cross-sectional study with 117 patients of both sexes, older than 18 years old. The group was made with migraine patients diagnosed by a neurologist according to the International Classification of Headache Disorders (ICHD) separated in two groups, one that has analgesics abuse and other that do not have. Three questionnaires were used: Barratt Impulsiveness Scale (BIS-11); Obsessive Compulsive Inventory-Revised (OCI-R) and the Migraine Disability Assessment (MIDAS). The data collected was placed in an electronic worksheet and processed in Software SPSS Statistics 22.0. There was an assumption of a p value of 0,05 to all cases with the intention to reject the null hypothesis. (To see the complete abstract, please, check out the PDF).